Green leaves of alfalfa used in therapeutical purposes - Sorin Jianu; Daniela Laura Buruiană; Ștefania Eliza Tănasie; Alexandru Chiriac (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
Medicago Sativa, also known as fodder for animals, has the propriety to increase the content of organic substance from the soil. After the biological, chemical and biochemical research on this plant, there was found an important/significant content of nutritive substances necessary for the human body and, used in various forms (as tea, juice, salads etc.), contributes in the same time as naturist medicine for human organism, or just in therapeutic forms for treating or improving diseases (as tinctures, capsules, powder etc.).sent the results obtained in order to determine the optimal moment for harvesting green leaves of Medicago sativa and the establishment of the maximum content in nutritive substances. Medicago sativa distinguished by the high content in enzymes, phytoestrogen, protein, Calcium, iron, magnesium, phosphorus, potassium, essential amino acids and vitamins C, B6, D, A, K and E (biologist Frank Bouer). Because the quantity of vegetal protein existing in the green leaves of the plant is higher than the one existing in the animal protein and the vitamin C is four times higher than in citrus (Gillian Mc Keith, 2008), the values of the two nutrients are determined in two different moments of leaf harvesting.
Keywords: 330; evolution; milk production; NW Region; Romania; trends